Status of Pacific Black Brant Branta bernicla nigricans on Wragel Island, Russian Federation - Ward, David H; Derksen, Dirk V; Kharitonov, Sergei P; Stishov, Mikhail; Baranyuk, Vasily V (Wildfowl, 1993)
AbundanceÂ , distribution, and habitat selection of breeding and moulting Pacific Black Brant were studied on Wrangel Island in 1989-91. Â Two nests and <10 family flocks of Brant were found during ground searches in previously known nesting areas. Â The breeding population has declined from 1000-2000 pairs to probably <100 pairs. Â An estimated 4200 Â 50 (Cl) moulting Brant were counted during the first aerial and photographic survey of the island in 1990. Â This population includes moult migrants from Alaska and mainland Russia. Â Most (67%) of the moulting flocks were concentrated in freshwater lakes and usually within 2 km of the coast. Â Lakes with low relief shorelines and adjacent preferred grasses were important habitats used by moulting birds. Â Breeding and moulting populations of Wrangel Island Brant are dependent on Izembek Lagoon Alaska, in autumn and disperse over the rest of eastern Pacific Flyway in winter and spring.